A Control Framework for the Proton Exchange Membrane Fuel Cell System Integrated the Degradation Information - Lei Fan; Jianhua Gao; Wei Shen; Hongtao Su; Su Zhou; Yiwei Hou (Energies)
To solve the control problem of the performance degradation of proton exchange membrane fuel cells (PEMFCs), a novel control framework based on the performance degradation is proposed. This control framework introduces the results of the state of health (SoH) estimation and remaining useful lifetime (RUL) prediction, which were used for the controller design because they determine the PEMFC output power. Furthermore, the information of SoH and RUL could be reflected the PEMFC health state and provided maintenance recommendations. The desired power of the stack was obtained, which was used as the real-time desired power of the PEMFC system by synthesizing the RUL, SoH, and ECU information of the stack. The results showed that when the PEMFC system used the designed control framework, the RUL and SoH information could be provided. The stack temperature showed an increasing and then decreasing trend, which indicates that the stack temperature was still controllable by controlling the speeds of the pump and fan.